Respuesta :

Space

Answer:

m = 2

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Step-by-step explanation:

Step 1: Define Equation

m - 4m = -6

Step 2: Solve for m

  1. Combine like terms:                    -3m = -6
  2. Divide -3 on both sides:              m = 2

Step 3: Check

Plug in m into the original equation to verify it's a solution.

  1. Substitute in m:                     2 - 4(2) = -6
  2. Multiply:                                 2 - 8 = -6
  3. Subtract:                                -6 = -6

Here we see that -6 does indeed equal -6.

∴ m = 2 is the solution to the equation.